Synechococcus Assemblages across the Salinity Gradient in a Salt Wedge Estuary - Xia, Xiaomin; Guo, Wang; Tan, Shangjin; Liu, Hongbin (Frontiers in Microbiology, 2017)
Synechococcus are the most abundant and widely distributed picocyanobacteria in the ocean. The salt-wedge type of estuary possesses the complete horizontal and vertical gradient of salinity together with other physical and chemical parameters. In order to reveal whether such a complex environmental gradient harbors a high diversity of Synechococcus, we investigated the abundance, taxonomic composition and pigment genetic diversity of Synechococcus in surface and bottom waters across the salinity gradient in a salt-wedge estuary by flow cytometric analysis and pyrosequencing of the rpoC1 gene and cpcBA operon (encoding phycocyanin). Synechococcus were ubiquitously distributed in the studied region, with clear spatial variations both horizontally and vertically. The abundance and diversity of Synechococcus were low in the freshwater-dominated low salinity waters. By pyrosequencing of the rpoC1 gene, we have shown that with the increase of salinity, the dominant Synechococcus shifted from the freshwater Synechococcus to the combination of phylogenetic subcluster 5.2 and freshwater Synechococcus, and then the strictly marine subcluster 5.1 clade III. Besides, the composition of Synechococcus assemblage in the deep layer was markedly different from the surface in the stratified waters (dissimilarities: 40.32%-95.97%, SIMPER analysis). High abundance of clade III Synechococcus found in the brackish waters may revise our previous understanding that strains of this clade prefers oligotrophic environment. Our data also suggested that both the phylogenetic subcluster 5.3 Synechococcus, a lineage that was not well understood, and subcluster 5.1 clade I, a typical cold water lineage, were widely distributed in the bottom layer of the estuary. Clade I detected in the studied region was mainly contributed by subclade IG. Analysis of the cpcBA operon sequences revealed niche partitioning between type 1 and type 3 Synechococcus, with type 2 distributed broadly across the whole environmental gradients. Our results suggest that the salt wedge estuary provides various niches for different lineages of Synechococcus, making it an environment with high Synechococcus diversity compared with adjacent freshwater and shelf sea environments.